Production of lipids from microalgae Spirulina sp.: Influence of drying, cell disruption and extraction methods. (October 2016) - Pohndorf, Ricardo S.; Camara, Álisson S.; Larrosa, Ana P.Q.; Pinheiro, Cláudio P.; Strieder, Monique M.; Pinto, Luiz A.A.
Abstract: The pretreatment operations (drying, cell disruption and oil extraction) of microalgae biomass to the lipids extraction are important steps to the product quality and production cost. In this study, the lipids from Spirulina were obtained by different methods of biomass drying (tray and spouted bed), cell disruption (microwave, autoclaving and milling) and solvent extraction (hot and cold). The average content of lipids extracted by the cold method, using polar solvents, was of 5.8 ± 0.6 g 100 g −1 . The spouted bed drying with cell disruption by milling achieved the best performance with the hot extraction method. Under these conditions, the TBA value was of 0.57 ± 0.09 mgMDA kg −1 . FT-IR spectra and thermal analysis indicated that the hot extraction resulted in a more purified lipid extract than the cold extraction. The Brimberg model showed the best fit to the lipid extraction kinetics and the activation energy in the best conditions was of 6.11 ± 1.41 kJ mol −1 . Graphical abstract: Highlights: Pretreatments of microalgae biomass for the production of lipids were evaluated. Spouted bed drying and milling increased the extraction yield of neutral lipids. Hexane showed a low extraction efficiency of total lipid, but extracted more the neutral lipids. More than 90% of the lipids were extracted in 60 min by hot extraction. Less energy was needed to extract lipids of Spirulina dried in spouted bed.